Review of The Temptations of Trade. Britain, Spain, and the Struggle for Empire, by Adrian Finucane - Oostindie, Gert (European Review of Latin American and Caribbean Studies, 2017)
The Temptations of Trade. Britain, Spain, and the Struggle for Empire, by Adrian Finucane. University of Pennsylvania Press, 2016.